Preparation and Characterization of Amino Acids-Based Trimethoprim Salts - Afzal R. Mohammed; Tony Worthington; Peter Hanson; Amr ElShaer; Peter Lambert (MDPI AG, 2012)
Trimethoprim (TMP) is a dihydrofolate reductase (DHFR) inhibitor which prevents the conversion of dihydrofolic acid into tetrahydrofolic acid, resulting in the depletion of the latter and leading to bacterial death. Oral bioavailability of TMP is hindered by both its low solubility and low permeability. This study aims to prepare novel salts of TMP using anionic amino acids; aspartic and glutamic acid as counter ions in order to improve solubility and dissolution. TMP salts were prepared by lyophilisation and characterized using FT-IR spectroscopy, proton nuclear magnetic resonance (1HNMR), Differential Scanning Calorimetry (DSC) and Thermogravimetric analysis (TGA). Both the amino acids formed salts with TMP in a 1:1 molar ratio and showed a 280 fold improvement in solubility. Investigation of the microbiological activity of the prepared salts against TMP sensitive Escherichia coli showed that the new salts not only retained antibacterial activity but also exhibited higher zone of inhibition which was attributed to improved physicochemical characters such as higher solubility and dissolution. The results are an important finding that could potentially impact on faster onset of antibacterial activity and reduced therapeutic dose when administered to patients. Studies are underway investigating the effect of ion-pairing TMP with amino acids on the permeability profile of the drug.